Hooked on weight control: An economic theory of anorexia nervosa, and its impact on health and longevity - Holger Strulik (University of Göttingen, Center for European, Governance and Economic Development Research (cege), 2021)
In this paper, I combine economic theories of health behavior and addiction in order to explain the phenomenon of anorexia nervosa and its impact on health and longevity. Individuals consume normal goods and foods and can work off excess calories with physical exercise. There exists a healthy body mass index and deviations from it increasingly cause health deficits due to obesity or underweight. There exists also a subjective target weight and being heavier than target weight causes a loss of utility from body image. Individuals for whom the utility loss from missing target weight is large exert more weight control, i.e. they eat less and exercise more. Anorexia is initiated in individuals who are particularly successful in weight control and prone to addiction. Addiction to weight control motivates anorexic individuals to perpetually adjust their target weight downwards and to eat less and exercise more. With declining weight, health deficits accumulate faster and mortality risk rises. I calibrate the model to a reference American with bmi 28. Due to weight loss addiction, the bmi gradually declines to a level of 15 and causes a loss of 21 years of life expectancy at the age of 20.
Keywords: D11; D91; E21; I10; I12; 330; weight control; addiction; eating disorder; physical exercise; healthde cits; mortality